Autogestão da dor crônica no processo de retorno ao trabalho: vivência de trabalhadores - João, Rosilene de Oliveira Rosa (Universidade Federal de São Carlos, 2024)
Introduction: chronic pain has a high prevalence in Brazil and around the world, and exerts significant impact on people’s lives, including the professional and social relationships dimensions. Strategies that promote self-management of pain and maintenance of work activities are useful for health professionals, managers and people with pain themselves, and should be investigated. Objective: to understand the chronic pain self-management strategies used by workers in the process of returning to work. Method: the study design included two stages. The first was a literature review aimed at identifying and synthesizing pain self-management strategies guided by PRISMA recommendations, conducted in the MEDLINE, WoS and Scopus databases, including studies published in Portuguese and English between 2017 and 2022, based on the descriptors “chronic pain” and “return to work”. In the second stage, a field study focusing on understanding the experiences of workers with chronic pain regarding their return to work was developed at the Health School Unit of the Federal University of São Carlos with the target audience: workers over 18 years old, regardless of sex, type of employment or occupation, undergoing rehabilitation care at the unit, with chronic pain for at least three months and who had returned to work after any period of absence. Data were collected through individual interviews guided by semi-structured questions and analyzed using thematic content analysis. Results: in the review, of the 14 studies included, ten indicate strategies for self-management of chronic pain predominantly focused on the individual through multidisciplinary programs, two have the participation of the work supervisor in the process, and two describe actions in the work environment as facilitators for returning to work. The results highlighted organizational weaknesses regarding support strategies and adaptations in the work environment. Participants in the field study were 12 workers, six of which were informal and/or self-employed, predominantly female and diagnosed with fibromyalgia. The analysis resulted in 27 recording units and the following thematic categories: aspects that contributed to pain; repercussions of pain on life and work; pain self-management strategies; facilitators and obstacles to returning to work. The results pointed to environmental and organizational aspects of work as contributing to the emergence or worsening of pain and among pain self-management strategies for returning to work, most were individual-focused and had little involvement of the organization in this process. Conclusion: in view of the pain self-management strategies brought by participants of this study, and the significant eases and difficulties in returning to work, the following are emphasized; individual focus, the absence of programs aimed at returning and maintaining work, lack of involvement of employers in sharing this responsibility, the need for adaptations in the workplace, as well as the lack of preparation of health professionals, in general, to care for workers with chronic pain.
Chronic pain self-management in the return-to-work process: workers’ experience
Keywords: Saúde do trabalhador; Dor crônica; Autogestão; Retorno ao trabalho; Workers health; Chronic pain; Self-management; Return to work; CIENCIAS DA SAUDE::ENFERMAGEM; CIENCIAS DA SAUDE::SAUDE COLETIVA; CIENCIAS DA SAUDE